PERAN MEDIASI KINERJA KEUANGAN TERHADAP HUBUNGAN ANTARA ASET TIDAK BERWUJUD TERHADAP KINERJA PASAR - Susanti Widhiastuti (Media Riset Akuntansi, Auditing & Informasi, 2016)
The purpose of this study was to analyze the effect of intangible resources against stocks return mediated by the financial performance. The research was conducted on Trade sector companies listed on the Indonesia Stock Exchange in the observation period 2012-2015. The number of samples taken by using purposive sampling method. Multiple regression analysis and path analysis was used to analyze the hypothesis in this study. This research has not been able to prove that there is a mediation role in financial performance in the relationship between the intangible resources and stock returns. This is due to the external factors that affect stock returns. However partially, both of intellectual capital and goodwill proven their effect on stock returns. The results also showed that intangible resources such as goodwill and enterprise risk management capabilities have a positive effect on the company's financial performance. Otherwise intellectual capital have not been able to show its influence on the financial performance.